Rock solid how the Philippines won its maritime case against China - Vitug, Marites Danguilan (BUGHAW, an imprint of Ateneo De Manila University Press, 2018)
"Rock Solid: How the Philippines Won Its Maritime Case Against China presents a comprehensive account of the epic legal success of the Philippines' territorial claim over that of China. the arbitral ruling is paramount to the protection of Philippine sovereignty and territorial integrity. Readers will appreciate the unpacking of the complex nature of Philippine national interest, stretching from fishery and natural resources to security concerns and territorial integrity of the nation"--Publisher's description.